1980
DOI: 10.1039/dt9800000269
|View full text |Cite
|
Sign up to set email alerts
|

Thermal decomposition of some alkali-metal oxalate monohydrates and monoperhydrates

Abstract: The kinetics of the decomposition of a series of alkali-metal oxalate perhydrates and their related hydrates have been studied by a combination of thermogravimetric analysis, differential scanning calorimetry, and optical microscopy. The behaviour of the perhydrates is strikingly similar to that of the related hydrate (where this exists). The kinetic formulations which best fit the decompositions have been ascribed and activation energies obtained for experiments carried out in a static atmosphere (€, = 64-208… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

1988
1988
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…The structure is built up of endless chains of alternating hydrogen peroxide molecules and oxalates ions linked together by hydrogen bonds. In 1980, Adams et al studied the thermal decomposition of Na 2 C 2 O 4 ·H 2 O 2 under isothermal conditions . Nevertheless, to the best of our present knowledge, further investigations on the compound Na 2 C 2 O 4 ·H 2 O 2 have not been reported in the literature.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…The structure is built up of endless chains of alternating hydrogen peroxide molecules and oxalates ions linked together by hydrogen bonds. In 1980, Adams et al studied the thermal decomposition of Na 2 C 2 O 4 ·H 2 O 2 under isothermal conditions . Nevertheless, to the best of our present knowledge, further investigations on the compound Na 2 C 2 O 4 ·H 2 O 2 have not been reported in the literature.…”
Section: Introductionmentioning
confidence: 93%
“…It is well-known that solid−liquid phase equilibrium data are important in crystallization processes. As described by Pederson and Pederson 2 and Adams et al, sodium oxalate reacted with hydrogen peroxide solution, and Na 2 C 2 O 4 ·H 2 O 2 crystallized from the system. Obviously, the preparing process of Na 2 C 2 O 4 ·H 2 O 2 was based on the phase diagram of the ternary Na 2 C 2 O 4 + H 2 O 2 + H 2 O system.…”
Section: Introductionmentioning
confidence: 94%
“…The interatomic dimensions of the oxalate ion are normal, but the ion is nonplanar. In 1980, Adams and co-workers 4 studied the thermal decomposition of (NH 4 ) 2 C 2 O 4 ‚H 2 O 2 under isothermal conditions. Nevertheless, to the best of the present authors' knowledge, further investigation on the adduct, (NH 4 ) 2 C 2 O 4 ‚ H 2 O 2 , has not been described elsewhere in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…It is well-known that solid-liquid phase equilibrium data are important in crystallization processes. Pederson and Pederson 3 and Adams et al 4 showed that ammonium oxalate can react with a hydrogen peroxide solution of a given concentration and that (NH 11 and demonstrate the temperature dependence of the ternary phase diagram.…”
Section: Introductionmentioning
confidence: 99%
“…Perhydrates are compounds which contain hydrogen peroxide of crystallisation and are important in bleach formulations for powder detergents. Much work has focused on sodium carbonate perhydrate [11] and the oxalate perhydrates [ 12]. However, little has been published on the properties of the isostructural inclusion compounds 4Na2SO4.MC1-2H202 (M=Na [13], K [14] and NH4 [15]).…”
Section: Introductionmentioning
confidence: 99%